IMPLEMENTASI KEBIJAKAN PEMBENTUKAN TIM TERPADU RELOKASI PASAR SAUMLAKI KABUPATEN MALUKU TENGGARA BARAT - Samrin Itranbey; Petronela Sahetapy; Jusuf Madubun (Jurnal Ilmiah Global Education, 2023)
The Tanimbar District Government's policy to replace traditional markets has received various responses from the public. Conflict over market management by the Olilit village government because it is the village's original source of income. The research method used was conducting in-depth interviews with local government and village communities. The research findings are (1). The local government has not considered the sources of economic income and employment for the village community. (2). The community refused to be relocated to the new market. (3). There needs to be socialization of regional spatial planning.